Effect of Y2O3 on the Microstructure and Properties of Selective Laser Melting TC4 Alloys - CHENG Yulong, LI Zhenhua, YIN Bo, HUANG Jieqing, ZHANG Yu, SONG Dudu (Cailiao Baohu, 2025)
The microstructure of TC4 titanium alloy prepared by selective laser melting(SLM) technology is prone to the phenomenon of coarse grains and poor wear resistance.To address this issue, an appropriate amount of Y2O3 was added during the SLM preparation process of TC4 titanium alloy, and its impact on the microstructure and properties of the resulting alloy was analyzed.Results showed that the appropriate addition of Y2O3 could significantly refine the microstructure of the TC4 titanium alloy, leading to improved mechanical properties and enhanced wear resistance.Compared to samples without Y2O3, when the Y2O3 content was 0.10%, the yield strength increased from 700 MPa to 1 086 MPa (a 55%increase), the tensile strength rose from 819 MPa to 1 255 MPa (a 50%increase), and the elongation decreased from 8.04%to 7.00%(a 12.9% reduction), which resulted in a good balance between strength and ductility.When the Y2 O3 content was increased to 0.15%, the microhardness of the TC4 titanium alloy increased from 308.8 HV to 377.1 HV (a 22%increase), indicating a significant improvement in wear resistance.In general,this study provided valuable theoretical insights and robust empirical evidence to support the enhancement of the mechanical properties of TC4 titanium alloys fabricated via SLM.